ISLAMIC SOCIAL REPORTING BANK SYARIAH DI INDONESIA : FOKUS PADA ISLAMIC GOVERNANCE SCORE, UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS DAN LEVERAGE - Budi Riyanti; Mukhammad Khukaim Barkhowa (Magister Manajemen STIE Bank BPD Jateng, 2021)
Sharia-based banking in carrying out its activities must be based on Islamic principles and teachings. A special framework is needed in social responsibility reporting so that it is in line with Islamic principles called Islamic social reporting. The development of social responsibility disclosures conducted by Islamic banks using the ISR index in Indonesia is still slow compared to Islamic countries in the world. The development of social responsibility disclosure reported by Islamic banks using the ISR index in Indonesia is still slow compared to Islamic countries in the world. The objective of this research is to determine the effect of Islamic governance score, company size, profitability, liquidity and leverage on Islamic social reporting. The sample used is a sharia commercial bank registered with the Financial Services Authority (OJK) 2016-2018. The analytical method used is multiple regression analysis. The results of this study indicate that Islamic governance score, firm size, profitability and liquidity have a significant positive effect on Islamic social reporting while leverage has a significant negative effect on Islamic Social Reporting.